ANALISIS HUKUM INTERNASIONAL TERHADAP PEMBERIAN SUAKA DIPLOMATIK KEPADA JULIAN ASSANGE OLEH KEDUTAAN BESAR EKUADOR DI INGGRIS - Pinasthika Puspitaningrum (BELLI AC PACIS, 2020)
This article analyzes the problems of granting diplomatic asylum to Wikileaks inventor and organization leader Julian Assange by the Ecuadorian Embassy in the UK according to International Law. Methodology and research used are normative research methods, namely research based on legal materials whose focus is on reading and studying primary and secondary legal materials. Based on the results of the study, the authors concluded that Julian Assange, as the leader of Wikileaks, leaked state secrets and diplomatic wires was an act that violated International Law. This action violates Article 10 paragraph 2 of the European Convention on Human Rights in 1950 which stipulates that in freedom of expression, there are limits to the types of information that can be disseminated in the general public, one of which is information concerning the interests of a State. The granting of diplomatic asylum to Julian Assange invited controversy, because for some countries, Julian Assange was labeled a political criminal, which caused that a political criminal, according to the 1954 Caracas Convention, was not permitted for any reason to be granted diplomatic asylum. The controversy over giving asylum was inseparable from the demands of the Swedish Court of Julian Assange involved in rape cases in Sweden, which allegedly was an alibi and political pressure from the countries concerned.